FRI0042 Anakinra improves functional status in patients with rheumatoid arthritis using methotrexate. (1st June 2001) - Cohen, SB; Woolley, JM; Chan, WW
Abstract : Background: Objectives: To evaluate the effect of anakinra, with respect to dose response and speed of effect, on the functional status of subjects with rheumatoid arthritis (RA) who were using methotrexate. Methods: In a large, multidose, placebo-controlled study of anakinra, 419 patients with active RA were randomised to receive, in addition to Methotrexate (MTX), either. 04 to 2.0 mg/kg of anakinra (daily SC injection) or placebo. Functional status was evaluated at baseline and after 4, 8, 12, 16, 20, and 24 weeks of therapy using the Health Assessment Questionnaire (HAQ). Comparisons between MTX alone and anakinra + MTX were analysed using change scores from baseline. Results: Patients receiving higher doses of anakinra experienced rapid and sizeable improvements in their HAQ scores. In percentage terms, HAQ scores improved more than 35 percent over baseline for the two highest doses (data not shown). These improvements occurred rapidly, were related to dose (p = 0.0014), and by week 4 the two highest doses were statistically significantly superior to placebo. Conclusion: In patients with active disease despite methotrexate therapy, the addition of anakinra led to rapid and clinically important improvements in functional status. These improvements were related to dose. Anakinra improves functional status in subjects with rheumatoid arthritis.